Farmacoeconomia e outcomes research - Attanasio, Ermanno (Farmeconomia. Health Economics and Therapeutic Pathways, 2004)
Pharmaceutical products are relevant for their contribution to the medicine progress and in health peoples improvement, altough this evidence goes back to the forthy years with the reduction in mortality, morbidity and hospitalisation rates. The ambivalence of drugs, both remedy and poison, needs a careful assessment of risks and benefits. Primitive estimates of health treatments evaluation occurred in the human history but the modern concept of evaluation in health care derived from cost-benefit analysis (welfare economics) and technology assessment. Then a new discipline, pharmacoeconomics and outcomes research, developed with the contribution of health economics, clinical medicine, pharmacology, statistics and epidemiology. Pharmaceutical products are also relevant because of their responsability of health expenditure growth. From 1992, in Italy, several legislative actions were made to face up the pharmaceutical expenditure. The most important one (L. 537/1993) achieved the maximum decrease of 16,8%, in 1994, and modified radically the pharmaceutical policy. Nevertheless, in the following six years the pharmaceutical expenditure grew more than 93%. New actions were made fixing the pharmaceutical expenditure to 13% of health expenditure, any excess being charged to Regions. In the new version for the current year, the excesses will be paid-back by pharmaceutical companies (60%) and Regions (40%). Furtherly, the creation of Agenzia Italiana del Farmaco increases the relevance of cost-effectiveness analyses for drugs reimbursement. However, pharmacoeconomic evaluations have still many methodological problems. Economic variables should be treated in the same manner of biomedical or epidemiological data, that is, by confidence intervals and sample sizes. There would be an “economic significance” besides to clinical and statistical ones. In this way, pharmacoeconomics and outcomes research would be able to add rationality to health care expenditure.